Examining small-scale cattle farmers’ willingness to participate in livestock auction markets in Bushbuckridge Local Municipality - Nyembe, Zanele Nonhlanhla; Hlongwane, Jan Johannes; Nengovhela, Rudzani (Talenta Publisher, 2025)
This study explored the willingness of small-scale cattle farmers in Bushbuckridge Local Municipality, Mpumalanga Province, South Africa, to participate in livestock auction markets. Agriculture, a cornerstone of economies, heavily relies on livestock farming in South Africa. However, small-scale cattle farmers face challenges in market participation. The study investigated the factors influencing farmers' willingness, emphasizing socio-economic characteristics. Using descriptive statistics and logistic regression, the research unveils significant factors, providing insights for targeted interventions. The logistic regression model indicates a statistically significant relationship between education level, farm size, access to agricultural information, farming experience, and farmers' willingness to engage in auction markets. Notably, higher education levels and larger farm sizes positively correlate with willingness, while increased access to agricultural information and excessive farming experience exhibit negative correlations. The findings have crucial implications for policy interventions, suggesting the need for educational programs to enhance farmers' awareness of auction markets, initiatives to increase farm sizes, and improved dissemination of agricultural market information.